A multi-component brazing filler metal for high-entropy of FV520B weld and a preparation method thereof
Patent Information
- Application Number
- CN202410883220.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-03
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-07-03
AI Technical Summary
[0002]FV520B钢是一种离心式压缩机风机叶轮叶片的母材材料,在采用传统手工熔焊焊接叶轮叶片狭窄弯曲的位置时不仅成本高效率低,还可能会产生焊接应力,使其焊缝处的热影响区成为风机叶轮叶片薄弱部位,在高速旋转时会受到应力的影响使其承受载荷较大,影响风机的使用寿命
[0013]与现有技术相比,本发明提供的用作钎焊FV520B不锈钢的多组元钎料是实现高熵化焊缝,多组元钎料配比为(CoCrNi)100-xMnx(x=20-35)。钎焊过程中焊缝与母材间的元素扩散无法避免,焊缝中的Fe元素会通过母材扩散至焊缝,与焊缝中向母材扩散后的各项元素达到平衡。在接头处形成CoCrFeNiMn高熵合金,使焊接接头形成焊缝高熵化。接头由焊缝中心区、扩散反应区与母材三部分组成,根据点扫描整体结果发现,在Mn含量为20%、25%、30%的焊缝中心区各个元素含量都在高熵合金规定的范围内,扩散熔合区为含有Co、Mn的CrFeNi基固溶体,也是以Cr0.19Fe0.7Ni0.11面心立方固溶体基体为主。本次实验采用的四种多组元钎料钎焊FV520B钢形成了良好冶金结合,界面结合良好,剪切强度呈现先增高后降低的趋势。含Mn量为25%和30%的接头断口形貌中的撕裂脊以及剪切韧窝说明接头发生的是韧性断裂,CoCrNiMn的剪切强度最高达到了199MPa。通过对钎焊接头进行EDS点分析可得,Mn元素虽对焊缝组织具有固溶强化作用,但焊缝中心的Mn含量相对较低,在剪切载荷作用下接头在钎缝中心位置最终发生断裂,断面上可观察到小而浅的韧窝以及一些脆性断裂的特征。
Smart Images

Figure CN118595676B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of alloy preparation technology, and in particular to a multi-component brazing filler metal for high entropy reduction of FV520B welds and its preparation method. Background Technology
[0002] FV520B steel is a base material for centrifugal compressor fan impeller blades. When using traditional manual welding to weld the narrow and curved parts of the impeller blades, it is not only costly and inefficient, but may also generate welding stress, making the heat-affected zone at the weld a weak point of the fan impeller blade. When rotating at high speed, it will be affected by stress, causing it to bear a large load and affecting the service life of the fan.
[0003] Compared with traditional fusion welding, brazing offers advantages such as simpler processes, higher production efficiency, and improved weld quality. However, it sometimes fails to achieve ideal weld strength when brazing stainless steel with traditional filler metals. This experiment will utilize a multi-component alloy as the filler metal and introduce the design concept of high-entropy welds. The four unique effects of high-entropy alloys can guarantee improved joint performance. To obtain higher-strength brazed joints, high-entropy welds represent a new research direction for theoretical development in the welding field. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides a multi-component brazing filler metal for high entropy reduction of FV520B welds and its preparation method.
[0005] To achieve the above objectives, the present invention is implemented according to the following technical solution:
[0006] One objective of this invention is to provide a method for preparing a multi-component brazing filler metal for high entropy reduction of FV520B welds, comprising the following steps:
[0007] S1, Molar ratio (CoCrNi) 100-x Mn x Take Mn elemental block powder and place it into a ball mill jar in sequence; where X = 20-35;
[0008] S2. Ball milling: After the metal powder and stainless steel balls are put into the ball milling jar at a ball-to-material ratio of 10:1, a vacuum is drawn and a small amount of n-heptane ethanol solvent is added to the jar as a process control agent to reduce the activity of the metal powder surface. Finally, ball milling is performed.
[0009] Furthermore, the purity of the Co, Cr, Ni, and Mn elemental powders is greater than 99.9%, and the particle size is 200 mesh.
[0010] Furthermore, in step S2, the ball milling process involves rotating for 30 minutes and then stopping for 10 minutes, with a rotation speed of 300 r / min and a milling duration of 60 h.
[0011] Furthermore, the ratio of stainless steel balls in the grinding jar is 3:2:1, with diameters of 15mm:10mm:5mm.
[0012] The second objective of this invention is to provide a multi-component brazing filler metal for high entropy reduction of FV520B welds prepared using the above method.
[0013] Compared with existing technologies, the multi-component brazing filler metal provided by this invention for brazing FV520B stainless steel achieves high-entropy welds. The multi-component brazing filler metal ratio is (CoCrNi). 100-x Mn x (x=20-35). Element diffusion between the weld and the base metal is unavoidable during brazing. Fe in the weld diffuses through the base metal to the weld, reaching equilibrium with the other elements that diffuse from the weld to the base metal. A CoCrFeNiMn high-entropy alloy is formed at the joint, resulting in a high-entropy weld joint. The joint consists of three parts: the weld center region, the diffusion reaction zone, and the base metal. Based on the overall point scan results, the element content in the weld center region with Mn contents of 20%, 25%, and 30% is within the range specified by the high-entropy alloy. The diffusion fusion zone is a CrFeNi-based solid solution containing Co and Mn, primarily composed of a Cr0.19Fe0.7Ni0.11 face-centered cubic solid solution matrix. The four multi-component brazing filler metals used in this experiment formed a good metallurgical bond in the brazing of FV520B steel, with good interfacial bonding. The shear strength showed a trend of first increasing and then decreasing. The tearing ridges and shear dimples in the fracture morphology of the joints with Mn contents of 25% and 30% indicate that the joints underwent ductile fracture, with the highest shear strength reaching 199 MPa for CoCrNiMn. EDS point analysis of the brazed joints revealed that although Mn has a solid solution strengthening effect on the weld microstructure, the Mn content at the weld center is relatively low. Under shear load, the joint eventually fractured at the center of the brazed weld, and small, shallow dimples and some brittle fracture characteristics were observed on the fracture surface. Attached Figure Description
[0014] Figure 1 The microstructure of the powder after ball milling for 60 hours is shown.
[0015] Figure 2 The XRD pattern of the powder after ball milling for 60 hours;
[0016] Figure 3 Optical microscopy (OM) images of brazed joints with different Mn content after being held at 1350℃ for 30 min;
[0017] Figure 4 SEM microstructure of brazed joints with different Mn content after being held at 1350℃ for 30 min;
[0018] Figure 5 Line scan elemental distribution diagrams of brazed joints with different Mn content after holding at 1350℃ for 30 min.
[0019] Figure 6 Surface scan elemental distribution diagrams of brazed joints with different Mn content after holding at 1350℃ for 30 min;
[0020] Figure 7 EBSD analysis of brazed joints with different Mn content after holding at 1350℃ for 30 min;
[0021] Figure 8 Particle size distribution of brazed joints with different Mn content after holding at 1350℃ for 30 min;
[0022] Figure 9 Fracture morphology of brazed joints with different Mn content after holding at 1350℃ for 30 min;
[0023] Figure 10 A statistical chart of the shear strength of brazed joints with different Mn content after holding at 1350℃ for 30 min.
[0024] Figure 11 Transmission electron microscope (TEM) images of brazed joints with different Mn content after being held at 1350℃ for 30 min. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. The specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.
[0026] Example 1
[0027] 1) Use an electronic balance with an accuracy of 0.01g and a molar ratio (CoCrNi). 80 Mn 20 Accurately weigh Co, Cr, Ni, and Mn elemental powders with a purity greater than 99.9% and place them into the ball mill jar in sequence;
[0028] 2) Cleaning the grinding jar and discharging the material: First, remove the dust and small particles left over from the last use from the grinding jar. Then, clean the grinding jar and put the prepared metal powders into the grinding jar in sequence.
[0029] 3) Ball milling: After placing the various metal powders into the ball mill jar, a vacuum is applied. The ball-to-powder ratio is 10:1. The stainless steel balls are loaded into the jar in a ratio of 3:2:1 (diameters 15mm:10mm:5mm). During ball milling, the mill is stopped for 10 minutes after every 30 minutes of rotation. The rotation speed is 300 rpm, and the milling time is 60 hours. A small amount of n-heptane-ethanol solvent is added to the jar as a process control agent to reduce the surface activity of the metal powders.
[0030] Example 2
[0031] The difference from Example 1 is that the molar ratio (CoCrNi) 75 Mn 25 Weigh the Co, Cr, Ni, and Mn elemental powders.
[0032] Example 3
[0033] The difference from Example 1 is that the molar ratio (CoCrNi) 70 Mn 30 Weigh the Co, Cr, Ni, and Mn elemental powders.
[0034] Example 4
[0035] The difference from Example 1 is that the molar ratio (CoCrNi) 65 Mn 35 Weigh the Co, Cr, Ni, and Mn elemental powders.
[0036] Figure 1 The image shows the microstructure of the powder after 60 hours of ball milling. It reveals a small portion of fragmented powder particles, unavoidable due to the limited number of grinding balls and the relatively large size of the mill jar. However, most of the elemental particles have aggregated into large, spherical particles, each formed by numerous smaller fragments welded together, with a size between 15-30 μm, significantly smaller than the original 200-mesh (74 μm) size of the individual metal powders. During ball milling, the metal balls continuously undergo intense microscopic compression and deformation against the powder surface, increasing the active sites, lattice defect density, and crystal interfaces. Through prolonged mechanical energy conversion and ball milling mixing, the powders of different metal elements are broken down, and the broken powder particles are bonded together through welding, thus achieving particle size reduction and homogenization.
[0037] Figure 2The XRD pattern of the powder after ball milling for 60 hours is shown. The FCC structure is composed of the CoCrNi phase. As the Mn content in the solder increases, the proportion of the CoCrNi phase decreases, and the diffraction peak of FCC shifts to the left. The peak formation of the HCP structure phase was also detected in the XRD, which is mainly composed of the Ni-rich Cr3Ni2 HCP phase structure. The peak intensity of HCP gradually decreases with the increase of Mn content in the solder.
[0038] Figure 3 Microscopic images of brazed joints with different Mn contents were obtained by holding at 1350℃ for 30 min. The filler metal melted and spread throughout the weld, forming a homogeneous solid solution phase. After corrosion, the weld and base metal showed a clear difference, with no cracks or voids. Experiments were conducted using vacuum brazing at 1350℃ with furnace cooling. Microscopic observation revealed dendritic structures in both the base metal and weld with Mn contents of 25%, 30%, and 35%. Dendritic formation was less pronounced at 35% Mn, while no dendrites formed at 20% Mn. However, the grain size of the base metal was larger than that of the base metals with other Mn contents, and the grains at the center of the weld were also relatively large. The width of the brazed joint gradually increased with increasing Mn content, reaching 79, 87, 93, and 98 μm respectively.
[0039] The formation of dendritic morphology in brazed joints is caused by the melting and filling of the filler metal within the joint gap. The molten filler metal and base metal dissolve and diffuse with each other, causing a metallurgical reaction in the brazed joint. This results in a large amount of Fe element from the base metal diffusing into the weld as an interstitial solid solution, leading to uneven chemical composition within the weld. However, the filler metal solidifies under furnace cooling conditions with a small temperature gradient, making the diffusion process between the filler metal and base metal very slow. The large supercooling, however, leads to the formation of dendritic phases within the grains, simultaneously promoting the formation of CoCrFeNiMn alloy welds. Microscopic observation revealed a diffusion reaction zone at the center of the base metal and weld, where dendritic structures connect the base metal and the weld center. The weld center exhibits a dendritic microstructure, and the size and morphology of the dendritic microstructure in the CoCrFeNiMn alloy at the weld varies with the Mn content. This phenomenon is consistent with the dendritic solidification of CoCrFeNiMn alloys first observed by Cantor et al.
[0040] Figure 4SEM microstructure images of brazed joints with different Mn content after holding at 1350℃ for 30 min are shown. The brazed joints consist of three parts: the weld center region (I), the diffusion fusion region (II), and the base metal. The images show that the brazed joint with a Mn content of 20% has a width of approximately 79 μm. The coarse grain formation at the weld joint is attributed to non-epitaxy growth at the interface. This growth connects some grains in the weld region with the grains in the stainless steel base metal, mainly due to the interdiffusion of elements in the brazing filler metal and the base metal, and the different bonding strengths of different elements in the crystal lattice. However, when the chemical composition and crystal structure of the base metal and the weld metal match, an interfacial reaction occurs. In the joints with Mn contents of 25%, 30%, and 35%, numerous irregular phases were found. The boundaries between the weld center region and the diffusion reaction region were difficult to observe through the microstructure images, and the entire fusion zone base was gray. After the brazing filler metal solidified, a small amount of dendritic phase was formed. At the center of the weld with a Mn content of 25%, a large number of densely packed black network phases appeared. Microscopic examination revealed dendritic segregation after alloying within the weld. Slight elemental differences existed between the dendrites; Ni and Mn tended to be distributed between the dendrites, while Co and Cr tended to be distributed within them. A small amount of white precipitates appeared at the stainless steel base metal, accompanied by trace amounts of carbon. At the center of the weld with a Mn content of 30%, a uniform dark gray phase was observed in the substrate. EDS elemental analysis at this point also revealed the formation of an Fe-based Cr0.19Fe0.7Ni0.11 solid solution phase. Furthermore, a large number of small, elongated grains were present at the interface between the base metal and the weld. The Fe content at this point was high, while the content of other elements, except for Cr, showed a significant decreasing trend. This is mainly due to the formation of these grains during brazing, where some nuclei adhered to the base metal interface and continued to grow—a non-epitaxy growth process. The alloying also exists in the weld center with a Mn content of 35%, exhibiting dendritic segregated phases. Both the weld center and the diffusion reaction layer are Fe-based solid solution phases.
[0041] Simultaneously, EDS point analysis was performed on the brazed joint. Besides high levels of Fe and Cr in the weld center region, there were also certain amounts of Co, Mn, and Ni. The Mn content in the weld matrix phase was significantly lower than the designed composition of the brazing filler metal. Furthermore, as the Mn content in the brazing filler metal increased, the Mn content in the brazed joint gradually decreased after brazing, while the Fe content gradually increased. The Fe content in the brazed joint was found to be lowest at the 20% MnA point (25.51%), with the highest Mn content at 13%. The Fe content was highest at the 35% MnG point (37.47%), with the lowest Mn content at 9%. The Mn content was significantly lower than that in the prepared alloy powder, mainly because Mn not only volatilizes but also undergoes segregation due to the high temperatures during brazing. Except for the significant trend in Mn content, the contents of other elements decreased to varying degrees with increasing Fe diffusion. The Fe content in the diffusion fusion zone is much higher than that in the weld center zone, reflecting the diffusion trend of matrix elements into the weld. Moreover, the higher the Mn content in the alloy powder, the higher the Fe content in the weld. Mn segregation will increase the diffusion of Fe.
[0042] In summary, it can be seen that the content of each element in the weld center area with Mn content of 20%, 25%, and 30% is within the range specified by the high-entropy alloy. The diffusion fusion zone is a CrFeNi-based solid solution containing Co and Mn, mainly composed of a Cr0.19Fe0.7Ni0.11 face-centered cubic solid solution matrix. The content of Mn, Co, and Ni elements in the diffusion fusion zone decreases significantly, while the Cr element content decreases less.
[0043] Figure 5 Line scan elemental distribution maps of brazed joints with different Mn contents after holding at 1350℃ for 30 min are shown. During brazing, interdiffusion of elements between the filler metal and the base metal forms a diffusion fusion zone with a thickness of approximately 20-30 μm at the interface. The width of the diffusion fusion zone increases with increasing Mn content. According to the binary phase diagram, Fe is infinitely soluble with Co, Cr, Ni, and Mn. Mn has a larger diffusion coefficient in Fe than other elements, resulting in a longer diffusion distance and greater diffusion amount in stainless steel. As the Mn content in the alloy powder increases, the diffusion tendency of Fe in the weld also increases, and the diffusion intensity of Mn also increases with the Mn content in the powder. The large amount of Mn diffusion segregation alters the microstructure of the entire brazed joint, potentially causing a transformation in the crystal structure of the interfacial diffusion layer from α-Fe in BCC to γ(Mn,Fe) in FCC.
[0044] Observation of the diffusion curves of Co, Ni, and Mn elements reveals that the content of Co and Ni elements in the weld center is lower than that in the accompanying gold powder. This is mainly due to the concentration gradient, which causes these two elements to diffuse from the weld to the base metal. The diffusion is most intense at the interface diffusion layer, with a peak appearing in the curve in the weld center region. At this point, the width of the weld center region is approximately 40 μm (the initial width of the weld), indicating that the elements have reached saturation and accumulated in large quantities in the weld center region during diffusion. The Cr element content in the weld decreases slightly, mainly because the Cr element content in the base metal and the weld is basically the same. Line scanning reveals that, except for Cr, which shows a plateau trend, the other elements show a trend of first increasing and then decreasing, or first decreasing and then increasing.
[0045] Figure 6 The image shows the elemental distribution of brazed joints with different Mn contents after holding at 1350℃ for 30 min. It can be seen that the elemental diffusion trends of the entire brazed joint are roughly the same for different brazing filler metals. This is mainly because the atomic radii of all elements are very similar, allowing each element to easily substitute for another, and each element can randomly occupy nodes in the crystal lattice to form a solid solution. Significant elemental diffusion occurs at the weld center, producing a large amount of Fe in the brazed joint. EDS surface scanning reveals that this Fe diffusion is mainly due to the large concentration gradient between the high content of basic elements in the stainless steel base material and the absence of Fe in the weld, leading to excessive Fe diffusion into the weld. This Fe diffusion shows a continuous increasing trend with different Mn contents; as the Mn content of the alloy powder increases, the Fe content at the weld center also increases after welding. EDS surface scanning of Cr content shows little difference between the brazed weld and the base material. The brazed weld contains large amounts of Co, Mn, and Ni, with lower contents from the weld center to the diffusion reaction zone, and less distribution in the base material. The Fe content in the weld gradually increases as the Co, Ni, Cr and Mn content in the brazing filler metal intermediate layer decreases, which means that the CoCrFeNiMn HEA intermediate layer and the base metal matrix achieve good solid solution metallurgical bonding.
[0046] Figure 7 EBSD analysis of brazed joints with different Mn contents at 1350℃ for 30 min is shown. The figures reveal an uneven interface between the weld and the base metal, primarily due to the heterogeneous nucleation of the melted filler metal during solidification. Newly formed nuclei adhere to the interface of the base metal and continue to grow. Furthermore, the grains in the base metal region are relatively fine, mainly because Cr-Fe precipitates form on the base metal during brazing, thus inhibiting grain growth.
[0047] Figure 8The image shows the grain size distribution of brazed joints with different Mn contents after holding at 1350℃ for 30 min. The figure shows that the smallest grain size in the joint is approximately 4 μm, and the largest is 104 μm, exhibiting a large size range. The largest proportion of grains are 20 μm and below. The average grain sizes in the brazed joints were measured to be 22.36 μm, 34.48 μm, and 45.92 μm, respectively. Furthermore, in joints with Mn contents of 25% and 30%, the largest grains, composed of equiaxed grains, were observed in the weld center region, while the diffusion fusion zone consisted of many irregular grains without a clear preferred orientation. In the joint with a Mn content of 35%, the element diffusion is the most intense. The Mn element in the brazing filler metal diffuses and segregates into the base metal, causing more Fe element in the base metal to diffuse into the weld. The diffusion fusion zone is the area with the largest Fe element diffusion. The atoms in this zone mainly grow through non-uniform nucleation based on the atoms attached to the base metal interface. As the Fe element is excessively melted in, the grains begin to grow and engulf the surrounding smaller particles, resulting in grain growth.
[0048] Figure 9 and Figure 10 Fracture morphology and shear strength statistics of brazed joints with different Mn content after holding at 1350℃ for 30 min are shown. Observation of the fracture morphology revealed that all four joints fractured at the center of the weld, indicating that the four medium-entropy brazing filler metals used in this experiment formed a good metallurgical bond with good interfacial adhesion, and the shear strength showed a trend of first increasing and then decreasing.
[0049] When the Mn content is 20%, the fracture morphology exhibits typical river patterns and cleavage steps, with some tongue-like patterns observed on the fracture surface. The shear strength is 190 MPa. The tearing ridges and shear dimples in the fracture morphology of the Mn contents of 25% and 30% indicate ductile fracture at the joint, with the highest shear strength reaching 210 MPa for CoCrNiMn. EDS point analysis of the brazed joint reveals that although Mn has a solid solution strengthening effect on the weld microstructure, the Mn content at the weld center is relatively low. Under shear load, the joint eventually fractures at the center of the brazed joint. Small, shallow dimples and some brittle fracture characteristics are observed on the fracture surface. As shown in the figure, the joint fractures in the Cr0.19Fe0.7Ni0.11 solid solution phase distribution area. Under shear force, stress concentration occurs in the Cr0.19Fe0.7Ni0.11 solid solution phase distribution area, leading to stress concentration in the brazed joint under shear load. The time from deformation to fracture is relatively short, so only local areas undergo plastic deformation, resulting in small and shallow dimples on the fracture surface. The fracture morphology with a Mn content of 35% is river pattern and cleavage steps, which indicates brittle fracture. The shear strength also decreases accordingly, reaching 195 MPa. At this point, the increased Mn content leads to increased dissolution and diffusion of the parent material, and the size of the brazed joint also increases. The increased width of the interfacial reaction layer causes stress concentration at the interfaces of each layer, which easily leads to cracks during shearing, weakening the brazed joint and reducing its strength.
[0050] Mn diffusion plays a role in solid solution strengthening in the brazed joint microstructure. However, the gradual widening of the weld seam hinders element diffusion, thus higher Mn content leads to poorer inhomogeneity in the brazed joint microstructure. Shear performance analysis shows that the brazed joint exhibits the highest shear strength at a relatively low Mn content of 25%.
[0051] Figure 11 Transmission electron microscopy (TEM) images of brazed joints with different Mn contents, held at 1350℃ for 30 min. TEM confirms the Ni-based HCP 1Cr3Ni2 solid solution phase structure (lamellar), HCP 2CoCr solid solution phase structure, and FCCCr0.19Fe0.7Ni0.11 solid solution phase structure detected by XRD. The polymorphic transformation from face-centered cubic (FCC) to hexagonal close-packed (HCP) structure in the CoCrFeMnNi high-entropy alloy prototype under high temperature and high pressure is irreversible. Pressure and temperature are generally the controlling parameters that induce these transformations by altering atomic and / or electronic structures and creating new materials. The FCC phase is a stable polymorph at high temperatures, while the HCP structure is more favorable at lower temperatures. The critical temperature for the HCP to FCC transformation also increases with increasing pressure.
[0052] In summary, the multi-component brazing filler metal provided by this invention for brazing FV520B stainless steel achieves high-entropy welds, and the multi-component brazing filler metal ratio is (CoCrNi). 100-x Mn x (x=20-35). Element diffusion between the weld and the base metal is unavoidable during brazing. Fe in the weld diffuses through the base metal to the weld, reaching equilibrium with the other elements that diffuse from the weld to the base metal. A CoCrFeNiMn high-entropy alloy is formed at the joint, resulting in a high-entropy weld joint. The joint consists of three parts: the weld center region, the diffusion reaction zone, and the base metal. Based on the overall point scan results, the element content in the weld center region with Mn contents of 20%, 25%, and 30% is within the range specified by the high-entropy alloy. The diffusion fusion zone is a CrFeNi-based solid solution containing Co and Mn, primarily composed of a Cr0.19Fe0.7Ni0.11 face-centered cubic solid solution matrix. The four multi-component brazing filler metals used in this experiment formed a good metallurgical bond in the brazing of FV520B steel, with good interfacial bonding. The shear strength showed a trend of first increasing and then decreasing. The tearing ridges and shear dimples in the fracture morphology of Mn content of 25% and 30% indicate that the joint underwent ductile fracture. The shear strength of CoCrNiMn reached a maximum of 199 MPa. EDS point analysis of the brazed joint revealed that although Mn has a solid solution strengthening effect on the weld microstructure, the Mn content in the weld center is relatively low. Under shear load, the joint eventually fractured at the weld center, and small, shallow dimples and some brittle fracture characteristics were observed on the fracture surface.
[0053] The technical solutions of the present invention are not limited to the specific embodiments described above. Any technical modifications made in accordance with the technical solutions of the present invention fall within the protection scope of the present invention.
Claims
1. A method for preparing a multi-component brazing filler metal for high entropy reduction of FV520B welds, characterized in that, Includes the following steps: S1, Molar ratio (CoCrNi) 100-x Mn x Take Co, Cr, Ni, and Mn elemental powder blocks and place them sequentially into a ball mill jar; where X = 20-35; S2. Ball milling: After the metal powder and stainless steel balls are put into the ball milling jar at a ball-to-material ratio of 10:1, a vacuum is drawn and a small amount of n-heptane ethanol solvent is added to the jar as a process control agent to reduce the activity of the metal powder surface. Finally, ball milling is performed.
2. The method for preparing the multi-component brazing filler metal for high entropy reduction of FV520B welds according to claim 1, characterized in that: The purity of the Co, Cr, Ni, and Mn elemental powders is greater than 99.9%, and the particle size is 200 mesh.
3. The method for preparing the multi-component brazing filler metal for high entropy reduction of FV520B welds according to claim 1, characterized in that: In step S2, the ball milling process involves rotating for 30 minutes and then stopping for 10 minutes. The rotation speed is 300 r / min, and the ball milling time is 60 h.
4. The method for preparing the multi-component brazing filler metal for high entropy reduction of FV520B welds according to claim 1, characterized in that: The ratio of stainless steel balls in the grinding jar is 3:2:1, with diameters of 15mm:10mm:5mm.
5. A multi-component brazing filler metal for high entropy reduction of FV520B welds prepared by the method described in any one of claims 1-4.
Citation Information
Patent Citations
Cobalt-iron-nickel-chromium-manganese high-entropy alloy brazing filler metal and preparation method thereof
CN110125573A